2013
DOI: 10.2753/jec1086-4415170404
|View full text |Cite
|
Sign up to set email alerts
|

Helpfulness of Online Product Reviews as Seen by Consumers: Source and Content Features

Abstract: Online product reviews are important determinants of consumers' purchase decision. Although prior research has articulated various benefits of online product reviews, there are few investigations into whether or not they are perceived as helpful by consumers. Product review helpfulness is conceptualized as a second-order formative construct, which is manifested by perceived source credibility, perceived content diagnosticity, and perceived vicarious expression of the product review. In this study, we conduct a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
199
1
12

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 283 publications
(220 citation statements)
references
References 69 publications
(129 reference statements)
2
199
1
12
Order By: Relevance
“…4) Content: Reviews that are concrete are found to be more helpful than abstract ones [37]. The argumentation included to support the opinion presented in the review, both in terms of density and diversity, was also found to be a significant predictor of review helpfulness [34].…”
Section: B Factorsmentioning
confidence: 98%
See 2 more Smart Citations
“…4) Content: Reviews that are concrete are found to be more helpful than abstract ones [37]. The argumentation included to support the opinion presented in the review, both in terms of density and diversity, was also found to be a significant predictor of review helpfulness [34].…”
Section: B Factorsmentioning
confidence: 98%
“…For all papers that were published prior to 2016, we only included those that had a number of citations that is above a certain threshold. The older the publication date the higher the threshold we Parallel with the majority average rating [24] Neutral polarity in text & Sentiment [28] Emotions [36] Content Concrete [37] Argumentation [34] Mixture of objective and subjective elements [21] Explained actions [38] Explained reactions [38] Proportion of product-descriptive statements [26] Proportion of reviewer-descriptive statements [26] Reviewer Reputation and rank [27][24] [23] Helpfulness of previous reviews [21][29] Identity information disclosure [27][39] Number of followers [31] Positive historical record [20] Level of expertise [31] Customer vs expert [37][34] Expressed innovativeness [32] set (3 citations for 2015, 7 citations for 2014, 15 citations for 2013, etc.). For 2016, we considered all the papers that were published when we did the search (early June) without restrictions on the number of citations.…”
Section: A Paper Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Li, M., Huang, L., Tan, C. & Wei, K. (2013) in their article named 'Helpfulness of online product reviews as seen by consumers: source and content features' found that product review is one of the most important indicators that reflects the extent to which consumers perceive the review in facilitating judgment or purchase decisions. A helpful product review significantly influences consumer purchase decisions.…”
Section: Review Of Literaturementioning
confidence: 99%
“…A recent business survey reported that 92% of online consumers read advisors' reviews before they make purchase decisions [1]. Literature also suggests that advisors' reviews significantly influence consumers' attitudes towards the products or sellers, which ultimately influence sales [2,3].…”
Section: Introductionmentioning
confidence: 99%